Association of the Modified Mediterranean Diet Score (mMDS) with Anthropometric and Biochemical Indices in US Career Firefighters - Romanidou, Maria (Nutrients, 2020)
The Mediterranean diet is associated with multiple health benefits, and the modified Mediterranean Diet Score (mMDS) has been previously validated as a measure of Mediterranean diet adherence. The aim of this study was to examine associations between the mMDS and anthropometric indices, blood pressure, and biochemical parameters in a sample of career firefighters. The participants were from Indiana Fire Departments, taking part in the “Feeding America’s Bravest” study, a cluster-randomized controlled trial that aimed to assess the efficacy of a Mediterranean diet intervention. We measured Mediterranean diet adherence using the mMDS. Anthropometric, blood pressure, and biochemical measurements were also collected. Univariate and multivariate linear regression models were used. In unadjusted analyses, many expected favorable associations between the mMDS and cardiovascular disease risk factors were found among the 460 firefighters. After adjustment for age, gender, ethnicity, physical activity, and smoking, a unitary increase in the mMDS remained associated with a decrease of the total cholesterol/HDL ratio (β-coefficient −0.028, p = 0.002) and an increase of HDL-cholesterol (β-coefficient 0.254, p = 0.004). In conclusion, greater adherence to the Mediterranean diet was associated with markers of decreased cardiometabolic risk. The mMDS score is a valid instrument for measuring adherence to the Mediterranean diet and may have additional utility in research and clinical practice.